Future of Transparent Wood: A Preliminary Review - En, Chong Pu; Othman, Siti Amira (Journal of Advanced Industrial Technology and Application, 2023)
The wood has unique structure and excellent mechanical properties. Wood is important natural source for human civilization. Wood is anisotropy structure. Wood was the important material and natural resource in human civilization. Wood is widely used in many sectors such as building, fuel, tools and other. In the ancient, wood played an important role in human cultural, economic, act and building. As a natural and sustainable material, wood has excellent mechanical properties cause by unique structures relative to its cost. Wood due to its natural growth can define as renewable and sustainable material. Due to the hierarchical and anisotropy structure, wood have properties of high strength, good durability, high moisture content and high strength. Wood is porous and fibrous structural tissue of wood. Roots and stems of wood made by natural cellulose fibres growing upward all the way to the top of canopy. This paper will present a preliminary review about the future of transparent wood.